Pengaruh Return On Asset dan Return On Equity terhadap Pertumbuhan Laba pada Perusahaan Otomotif yang Terdaftar di Bursa Efek Indonesia Periode 2020-2023 - Ranti Fauziah; Taat Kuspriyono (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
As time goes by, the global economy is advancing and increasing competition/competence in the business world, encouraging business people who have a contribution in the development of a business, it is important for companies to know how the financial situation in the company. All parties involved with the company, both outside and inside, have an interest in knowing information related to business owners. Periodically published profit data, such as semi-annual and annual reports, can be a useful tool to assess a company's financial health. For stakeholders who need to make economic decisions, financial statements play a very important role in decision making, namely as a source of information for parties other than the company. The value of financial statement information in decision making will be even more useful if the data presented is able to predict future events.